2023
DOI: 10.3390/ma16093472
|View full text |Cite
|
Sign up to set email alerts
|

Phytosynthesis of Silver Nanoparticles Using Leonurus cardiaca L. Extracts

Abstract: The present work describes, for the first time in the literature, the phytosynthesis of silver nanoparticles using Leonurus cardiaca L. extracts. The influence of the extraction method (classical temperature extraction and microwave extraction), as well as of the extract concentration on the characteristics of the nanoparticles, was studied using analytical methods, such as UV-Vis spectrometry, X-ray diffraction, dynamic light scattering, and transmission electron microscopy. Experimental data suggest that use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 63 publications
1
14
0
Order By: Relevance
“…The solutions were kept at room temperature and ambient conditions, without any stirring. The formation of silver nanoparticles can be visually monitored by the apparition of a specific ruby-red color [31,32]. After 24 h, the NPs suspensions were immediately analyzed by UV-Vis spectrophotometry, and the remaining solutions were preserved in the dark at 4 • C and further used for the described tests.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The solutions were kept at room temperature and ambient conditions, without any stirring. The formation of silver nanoparticles can be visually monitored by the apparition of a specific ruby-red color [31,32]. After 24 h, the NPs suspensions were immediately analyzed by UV-Vis spectrophotometry, and the remaining solutions were preserved in the dark at 4 • C and further used for the described tests.…”
Section: Methodsmentioning
confidence: 99%
“…The total phenolics content was determined using a colorimetric method (Folin-Ciocâlteu reagent method), as previously described [31,32], involving the formation of a blue complex upon the reduction of the Folin-Ciocâlteu reagent by phenolics present in the extracts. The Folin-Ciocâlteu reagent (Merck KGaA, Darmstadt, Germany) and sodium carbonate solution (Merck KGaA, Darmstadt, Germany) were commercially available and used without any purification.…”
Section: Characterization Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Traditional Chinese Medicine has made certain progress in preventing and treating DR. 17 Leonurus heterophyllus has been applied in the clinical treatment of gynecological and obstetric diseases. 18 Stachydrine (STA) is a water-soluble alkaloid extracted from Leonurus heterophyllus , which can inhibit cell apoptosis, maintain myocardial cell homeostasis, and reduce endothelial dysfunction. 19 , 20 Recently, research found that STA was an effective compound of Tangwang Mingmu granule, which was a traditional Chinese medicine and widely used in the DR treatment.…”
Section: Introductionmentioning
confidence: 99%